Characteristics of patients associated with antibiotic use among gastrointestinal surgery at the Academic Hospital, Universitas Gadjah Mada - Saskiya, Pingki Arum; Taufiqurohman; Wiedyaningsih, Chairun (Published by Universitas Gadjah Mada, 2024)
Digestive surgery is a treatment for diseases of the parts of the body involved in digestion, which has a fairly high risk of infection. The study aimed to obtain a description of the types and specific characteristics of patients and the rationality of antibiotic use among digestive surgery patients. This study was conducted using observational analysis. Data on antibiotic use was collected prospectively from medical records of digestive surgery inpatients at the Academic Hospital Universitas Gadjah Mada (UGM) from January to March 2023. The Gyssens method was used to evaluate qualitatively the use of antibiotics. A total of 76 patients met the inclusion and exclusion criteria. No significant difference between the number of male and female patients was identified. The results showed that 24 (31.58%) acute appendicitis patients are the primary diagnosis most often encountered in patients undergoing digestive surgery. The most frequently used prophylactic antibiotics for digestive surgery patients were ceftriaxone (53.85%) and cefazolin (41.03%). Meanwhile, the most frequently used therapeutic antibiotics were ceftriaxone (41.94%) and levofloxacin (29.03%). The Gyssens analysis shows that large irrational use of antibiotics is still observed.